MANAJEMEN SUMBER DAYA MANUSIA PADA ORGANISASI (Studi Kasus: Jack Nelson Direksi Bank Lokal X) - Eka Mayasari Siswi Ciptaningsih (Universitas Pamulang, 2015)
HUMAN RESOURCE MANAGEMENT IN ORGANIZATIONS (CASE STUDY: JACK NELSON OF BANK DIRECTORS LOCAL X). This paper analyzes the circumstances that occurred on the banks X related to human resources which have a very high growth. Allegedly this high growth happens when each branch has the authority for the recruitment of employees and their numbers are very high turnover in employees. Base on the analysis this circumtance will be linked to the concept of human resource management reorganization at the central, the planning, the recruitment process and strategy, as well as training and development of employees. So it would appear that the new system will build either through reorganization, labor planning, recruitment process systemically, as well as employee development training . That will be no misscommunication and there is no iut of procedure will occure. Keywords: reorganization, job descriptions, recruitment task analysis, training, developing of employees.